SISTEM PENUNJANG KEPUTUSAN TERHADAP PILIHAN PRODUK UNTUK MENINGKATKAN KEPUASAN PELANGGAN BERBASIS WEB (Studi Kasus : PT. Autochem Industry Cabang Bogor Raya) - Fuad Fahmi; Yudi Kurniawan (CV. Multi Kreasi Media, 2024)
Customer satisfaction is a crucial factor for business sustainability and growth, including at PT Autochem Industry Bogor Raya Branch. The process of selecting the right product is often a challenge for customers, which can have an impact on satisfaction levels. This research aims to develop a web-based Decision Support System (DSS) that can assist customers in selecting products that suit their needs, thereby increasing customer satisfaction. This DSS is built by considering various product selection criteria, such as quality and boiling point. The data collection methods used include interviews with several staff of PT Autochem Industry Bogor Raya branch, observation, and literature study. The results show that the implementation of web-based DSS can make it easier for customers to choose the right and suitable product, which ultimately contributes to increased customer satisfaction.